2017
DOI: 10.1002/bip.23025
|View full text |Cite
|
Sign up to set email alerts
|

Lysine to arginine mutagenesis of chlorotoxin enhances its cellular uptake

Abstract: Chlorotoxin (CTX), a disulfide-rich peptide from the scorpion Leiurus quinquestriatus, has several promising biopharmaceutical properties, including preferential affinity for certain cancer cells, high serum stability, and cell penetration. These properties underpin its potential for use as a drug design scaffold, especially for the treatment of cancer; indeed, several analogs of CTX have reached clinical trials. Here, we focus on its ability to internalize into cells-a trait associated with a privileged subcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…The latter peptide had stronger activity than the all-lysine one against both promastigotes and amastigotes of the different species/strains of Leishmania parasites tested (27 to 71 µM for promastigotes; 16 to 18 µM for amastigotes); moreover, p–Ac1R7 displayed a faster parasite membrane-permeation action than p–Ac1 [ 42 ]. These observations are in line with studies involving antimicrobial and anticancer peptides that have shown a greater capacity to penetrate cells when having a high density of arginine residues, as compared to analogs of the same length containing lysines instead [ 85 , 86 ].…”
Section: Understanding the Primary Structure And Composition Of Leishmanicidal Peptidessupporting
confidence: 82%
“…The latter peptide had stronger activity than the all-lysine one against both promastigotes and amastigotes of the different species/strains of Leishmania parasites tested (27 to 71 µM for promastigotes; 16 to 18 µM for amastigotes); moreover, p–Ac1R7 displayed a faster parasite membrane-permeation action than p–Ac1 [ 42 ]. These observations are in line with studies involving antimicrobial and anticancer peptides that have shown a greater capacity to penetrate cells when having a high density of arginine residues, as compared to analogs of the same length containing lysines instead [ 85 , 86 ].…”
Section: Understanding the Primary Structure And Composition Of Leishmanicidal Peptidessupporting
confidence: 82%
“…Accordingly, cellular uptake of TM601 in U373 glioma cells was a rapid concentration-and time-dependent process, which was affected by chlorpromazine, a pharmacological inhibitor of clathrin-mediated endocytosis, involved in the transport of coated pits. Interestingly, as in the case of lycosin-I from spider venom, the replacement of Lys with Arg in the CTX sequence, as observed with the synthetic analogs [K15R/K23R]CTX and [K15R/K23R/Y29W], enhanced its cellular uptake, as demonstrated in human cervical carcinoma (HeLa) cells with fluorescent derivatives [95].…”
Section: Chlorotoxinmentioning
confidence: 81%
“…However, given that CTX-3 binds to both a tumor cell line and a normal cell line, in contrast to previous studies on CTX, it appears likely that this region is not sufficient by itself to account for the selective binding to tumor cells. It is possible the cell surface binding observed for CTX-3 is non-specific membrane binding mediated by the presence of the high proportion of positively charged (two lysine and one arginine) residues within a seven-residue peptide as reported for other highly charged peptides (Futaki et al., 2007; Ojeda et al., 2017). Although no cell surface binding was observed for CTX-4, it was the only fragment that appeared to be specifically internalized into the glioma cells at 37°C.…”
Section: Discussionmentioning
confidence: 92%